THE RELATIONSHIP OF ORGANISATIONAL COMMITMENT, JOB SATISFACTION, AND ORGANISATIONAL CULTURE ON EMPLOYEE PERFORMANCE: AN EMPIRICAL STUDY AT PT. PUNGKOOK INDONESIA ONE GROBOGAN - Almaidah, Siti; Nurjanah, Arlinda (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Effective employee management is one of the critical components of business operations. This achievement is marked by a conducive working atmosphere and improved employee and organisational performance. The rapid changes that occur in the business world result in companies facing various forms of challenges. Companies are required to have an advantage. Employees have a major contribution to realizing these achievements by improving their performance. The aim of this research was to test and analyze the effect of organisational commitment, job satisfaction, organisational culture on the performance of employees of PT Pungkook Indonesia One Grobogan, Central Java. The sample involved was 95 employees. Sampling technique using accidental sampling. Data collected through questionnaires. Data analysis methods include instrument tests, classical assumption tests, multiple linear regression analysis, model feasibility tests, determination coefficient tests, and hypothesis testing. The findings in the research stated that employee performance is influenced by organizational commitment, job satisfaction, organizational culture. Keywords: employee performance, job satisfaction, organisational commitment, organisational culture